Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

Baby-Nath24

  • 2 years ago

Solve the quadratic equation by factoring 12x^2-3x-9=0

  • This Question is Closed
  1. ganibl
    • 2 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    12x^2 - 12x + 9x - 9 = 0 12x (x - 1) + 9 (x - 1) =0 (12x + 9) (x - 1) = 0 12x + 9 = 0 x - 1 = 0 x = -9/12 x = 1

  2. Baby-Nath24
    • 2 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    Thank You.

  3. Dubai_boy
    • 2 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    another way : factor the exact number for 12,3,9 which gives u 3 3(4x^2-x-3)=0 3(x-1)(4x+3)=0 3=0 x-1=0 >>> x=1 4x+3=0 >>> 4x=-3 >>> x=-3/4

  4. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy